ТИЛШУНОСЛИК ТАҲЛИЛ МЕТОДЛАРИ: ИНДУКЦИЯ ВА ДЕДУКЦИЯ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article, which is devoted to the discussion of issues related to the nature of language construction, the essence of linguistic units, talks about a number of current problems in the science of modern linguistics. Taking into account that the effectiveness of any scientific research depends on the chosen methods of analysis and the theoretical justification of these methods, the main attention is focused on the methodology of linguistic analysis.
Keywords: method, methodology, induction, deduction, empirical.